Combined thermal and electromigration exposure effect on SnAgCu BGA solder joint reliability - Luhua Xu; Pang, J.H.L. (56th Electronic Components and Technology Conference 2006, 2006)
Research of thermal, mechanical and electrical effect on lead free solder joints is very important for understanding the reliability of electronic package like BGA assemblies. Combined thermal and electromigration (EM) exposure on SnAgCu BGA solder joint reliability were reported. PBGA assemblies which were soldered on PCB board experienced thermal aging and Thermal-EM combined aging with current density of 10 3 to 10 4 A/cm 2 . Upon complete of the aging tests, solder were cross-sectioned and observed by scanning electron microscopy (SEM). In-situ temperature measurement were conducted on BGA packaging when the sample subject to combined thermal and EM exposure. Infrared thermal imaging system was used to determine the 2D temperature distribution in solder joint interconnects. The DC signal was passing through with a high current density of 10 3 -10 4 A/cm 2 . Higher temperature was observed on the solder joint compared to the background. At the corner of the solder joint, the temperature increment could reach more than 100 degC when the current density is about 3times10 4 A/cm 2 . This is due the current-crowding effect at the corner and it causes higher joule heating. Since the EM phenomena at high temperature are even more significant, void process could occur first at these locations. The impact of EM on the growth of interfacial IMC in Ni/SAC/Ni and Cu/SAC/Ni solder joint was observed. It was found IMC layer growth on anode interface is faster than cathode interface, and both are faster than isothermal aging. The in-situ strain in the BGA solder joints subject to thermal-electrical loading were measured by micro digital image speckle correlation system (Micro-DISC), the system is constructed based on the principle of DISA measurement. Large shear strain was observed at the corner of the solder joint when the solder joint is subject to pure temperature ramp up. Normal strain could be seen also when current was applied